2018
DOI: 10.1007/s00432-018-2590-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk for cancer in living kidney donors and recipients

Abstract: Kidney transplantation was associated with an increased risk of cancer during a long-term follow-up. Long-term risk for cancer in LKDs and kidney recipients should be monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…It is suggested that the safety of kidney donation should be carried out by long-term follow-up. In a recent study, Wang et al reported that RT is associated with an increased risk of cancer during long-term follow-up (36). Mortality data from the United States and other countries have identified cancer as the leading cause of death among living renal donors.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the safety of kidney donation should be carried out by long-term follow-up. In a recent study, Wang et al reported that RT is associated with an increased risk of cancer during long-term follow-up (36). Mortality data from the United States and other countries have identified cancer as the leading cause of death among living renal donors.…”
Section: Discussionmentioning
confidence: 99%
“…Diet has been implicated in long-term health outcomes in living kidney donors. A systematic review and meta-analysis of eight studies revealed that living kidney donors had 2.8 times greater odds of incidence of malignancy compared to nondonors after a follow-up between 18 months and 20 years [23]. A recent large retrospective cohort study using the Scientific Registry of Transplant Recipients (SRTR) linked with Surveillance, Epidemiology, and End Results (SEER) registry data revealed that the incidence of colorectal and kidney cancers were up to 2 and 3 times greater in living kidney donors compared to Adventist Health Study-2 (AHS-2) participants, respectively [24 ▪▪ ].…”
Section: Prevention For Declined Kidney Function Of the Donormentioning
confidence: 99%